Report on four cases of the rarest benign splenic tumor - myoid angioendothelioma, with literature review - Milosavljević Vladimir; Grubor Nikola; Matić Slavko; Erić Dragan; Tadić Boris (Srpski Arhiv za Celokupno Lekarstvo, 2021)
Introduction. Myoid angioendothelioma of the spleen is an extremely rare form of a benign splenic tumor. There is no characteristic symptomatology for this disease. Case outline. We present four patients operated on for myoid angioendothelioma of the spleen. Three patients were without problems while one had nonspecific problems. Two patients underwent laparoscopic surgery and two underwent open splenectomy. In all patients, the definitive diagnosis was confirmed by histopathological examination. By reviewing the aforementioned medical databases of published papers in English, we found a total of eight cases of myoid angioendothelioma of the spleen. In addition to the mentioned number, we have added our series of cases. Conclusion. Twenty-one years after the discovery of myoid angioendothelioma of the spleen, the small number of cases presented in the literature is still a limiting factor in making conclusions and in learning lessons about this disease